BANK SAMPAH ASOKA DALAM PENINGKATAN PENDAPATAN MASYARAKAT CLUSTER IXORA - Raisya Puspa Septiani (Institut Bisnis Muhammadiyah Bekasi, 2022)
Garbage is an environmental problem that until now there is no solution to in Indonesia. The waste bank is an effort to fix and improve the system waste management. The waste management system with a waste bank emphasizes recycling activities, especially plastic waste, cartons, cans, and so on. The purpose of a waste bank established in residential areas is to build public awareness of waste management, create a clean, healthy environment and change waste to be more useful in society such as making crafts and increasing additional income. With the Waste Bank, the benefits obtained from residents are being able to maintain cleanliness and environmental health, help the community's economy and build relationships between residents and build public awareness to care for the surrounding environment. This research used a qualitative approach with descriptive methods. Research informants were selected by purposive sampling. Research data were collected by observation, interview, and documentation study. The impact of the Ashoka waste bank program on the income of the community is that it can help the community to finance activities carried out in the environment without spending personal funds.